Osteonecrosis and osteomyelitis of the jaw associated with tumour necrosis factor-alpha (TNF-α) inhibitors: a systematic review. Issue 1 (January 2020) - Sacco, R.; Shah, S.; Leeson, R.; Moraschini, V.; de Almeida Barros Mourão, C.F.; Akintola, O.; Lalli, A.
Abstract: Tumour necrosis factor-α (TNF-α) inhibitors are increasingly being used as immunomodulators to manage inflammatory conditions such as rheumatoid arthritis and Crohn's disease. Reported serious side effects include an increased incidence of lymphoma and greater susceptibility to infections such as tuberculosis. The aim of this systematic review was to find out whether there is an associated risk of medication-related osteonecrosis of the jaw (MRONJ). Three authors independently searched PubMed, MEDLINE, EMBASE, CINAHL and the Cochrane Central Register of Controlled Trials for published reports of oral osteonecrosis (ONJ) or osteomyelitis (OM) in patients who took anti TNF-α drugs and had no history of antiangiogenic agents or antiresorptive treatment. All types of studies on humans treated with TNF-α inhibitors were considered. Only six were eligible for analysis, and all were independently assessed for risk of bias. They included six patients with ONJ or OM that was attributed solely to TNF-α inhibitors. The most common site of ONJ was the posterior mandible (n = 5). The mean (SD) duration of anti-TNF-α treatment before the development of bony lesions was 62.5 (47.4) months. Invasive surgery was reported as a precipitating factor in five cases, and the ONJ/OM resolved with conservative management in five. Although all the studies were judged to be at high risk of bias, the limited data suggest that some patients will potentially develop ONJ/OM as a result of treatment with TNF-α inhibitors. Studies of higher quality are now needed to establish the relative risk of MRONJ in patients who take them.